Development of Reading Materials with Coastal Culture Tapanuli Central for School Literation Movement in Basic School Pandan District - Hamdani, Hamdani; Sriadhi, Sriadhi; Eviyanti, Evi (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
The purpose of this study was to determine: (1) The results of the design of reading materials with coastal culture for literacy sources, (2) The results of expert validation on the design of reading materials containing coastal culture for literacy sources, and ( 3) The results of testing of reading materials with coastal culture. for literacy sources in Class V Elementary School, Pandan, Tapanuli Tengah. This type of research is the type of research development or Research & Development. The development model in this study will be made with a few modifications adapted to the Borg and Gall development procedure. Development research is generally divided into 3 (three) stages, namely the problem identification stage, the design stage, and the dissemination stage. The researcher attempted to adapt the development model to Borg and Gall's development procedures. As subjects in this study are all State and Private Elementary Schools in Pandan, Tapanuli Tengah. As the object of this research, developing reading materials based on the culture of the coastal communities of North Tapanuli Tengah Regency in supporting the School Literacy Movement. The results showed: (1) reading material with Tapanuli Tengah coastal culture is valid for use in the implementation of the school literacy movement in SD Pandan District.